Development of glass-based microfluidic devices: A review on its fabrication and biologic applications. (January 2023) - Aralekallu, Shambhulinga; Boddula, Rajamouli; Singh, Vijay
Graphical abstract: Glass based microfluidic device discussed with their merits, different fabricated materials and utilization in sensing, detection and biological applications. Highlights: Brief history of microfluidics and milestone development of glass-based microfluidics. Glass materials for device fabrication including organic materials. Embedded glass microfluidics and their fabrication. Sensing and detection of materials via optical, electrochemical, and spectroscopic detection methods. Immunoassays molecular biology analysis and drug delivery. Abstract: The advent of glass-based microfluidic devices further revolutionized in microfluidic technology due to the several advantageous properties in terms of photonics, electronics, and thermochemistry, compared to silicon, PDMS and paper. In this review article, we discuss the glass materials in comparison with inorganic, organic polymeric and paper materials for the fabrication of microfluidic devices and the suitability, benefits, applicability of their applications. We highlight the performance enhancement of glass achieved via hybrid fabrication with advanced polymers. For this comprehensive overview of the different materials for the fabrication and applications of microfluidic devices, we consider recent advances in the selected applications of glass material-based microfluidics in sensing and biomedical applications, such as Raman spectroscopy, mass spectroscopy, optical detection methods, embedded glass microfluidics for oil and gas, point-of-care diagnostics, cell analysis, nucleic acid assay, immunoassay analysis and drug delivery. Our review concludes by summarizing the future challenges and developments of these glass-based microfluidic devices.